PENGARUH BIAYA ANGKUT UTAMA (MAIN CARRIAGE) DAN HARGA JUAL EKSPOR TERHADAP VOLUME EKSPOR BARECORE KE CHINA DAN TAIWAN (Studi Kasus Pada Transaksi Ekspor PT. Albasia Sejahtera Mandiri Temanggung dengan Incoterms CFR tahun 2012-2016) - Ardy Wibowo; Putut Haribowo; Paniya Paniya (JOBS (Jurnal Of Business Studies), 2017)
The aim of this study is to explain the influence of Main Carriage and Export Price tothe exports volume of Barecore to China and Taiwan both simultaneously and partially. Thestudy utilized the primary data from PT. Albasia Sejahtera Mandiri. The research exploredthe multiple linier regression statistic analysis. The result of t-Test showed that export pricesof Barecore influence significantly to the Barecore’s export volume, while the MainCarriage was not influence significantly to the export volume of Barecore. The result of theF-Test showed that the Main Carriage and export prices of Barecore simultaneouslyinfluence to the export volume of Barecore significantly.It is recommended that in order to increase the exports volume of Barecore, PT. AlbasiaSejahtera Mandiri needs to pay more attention to export prices that they offer for importersbecause the export price was the most dominant influential variable in this study. Besidethat, other things that should be noted by PT Albasia Sejahtera Mandiri that in order toimprove export performance, it was necessary to pay attention to the demand andpurchasing power of export destination countries, government policy on tariff and non-tariffpolicy, inflation, exchange rate, per capita income of destination country and other that notuncontrolled. Moreover, factors affecting export performance include uncontrolled microenvironmental factors such as suppliers, competitors, and customers. Besides macroenvironmental factors such as economic, technological, demographic, and socio-cultural